2019
DOI: 10.4028/www.scientific.net/df.21.29
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Rates of Components in Metal-Silicides Depending on Atomic Number of Refractory Metal Component

Abstract: Interdiffusion studies conducted in group IVB, VB and VIB metal-silicon systems are discussed in detail to show a pattern in the change of diffusion coefficients with the change in atomic number of the refractory metal (M) component. MSi 2 and M 5 Si 3 phases are considered for these discussions. It is shown that integrated diffusion coefficients increase with the increase in atomic number of the refractory component when the data are plotted with respect to the melting point normalized annealing temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…HfSi 2 with a layered structure (space group Cmcm) is structurally isotypic with many transition-metal disilicides and digermanides, such as ZrSi 2 , ZrGe 2 , and HfGe 2 . 24,39,40 The refined lattice parameters at ambient conditions are a = 3.668 ± 0.001 Å, b = 14.534 ± 0.004 Å, and c = 3.639 ± 0.001 Å, yielding a unit cell volume of 194.0 ± 0.1 Å 3 , which is consistent with the result from previous studies on powdered samples 41 and slightly smaller than the reported value for a single crystal 40 (Table 1).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…HfSi 2 with a layered structure (space group Cmcm) is structurally isotypic with many transition-metal disilicides and digermanides, such as ZrSi 2 , ZrGe 2 , and HfGe 2 . 24,39,40 The refined lattice parameters at ambient conditions are a = 3.668 ± 0.001 Å, b = 14.534 ± 0.004 Å, and c = 3.639 ± 0.001 Å, yielding a unit cell volume of 194.0 ± 0.1 Å 3 , which is consistent with the result from previous studies on powdered samples 41 and slightly smaller than the reported value for a single crystal 40 (Table 1).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…16 c)) triggered by the inward diffusion of the Si to the Mo-Si interlayer. Since Si has a high diffusion rate in Mo, it diffuses towards the substrate alloys despite the Si oxide formation which leads to Kirkendall pores [47,48]. In the remaining area of the Si top layer of CS1, uniformly distributed porosities can also be seen after 10 hours, which agglomerate with increasing oxidation.…”
Section: Interdiffusion Processes Between the 3-phase And 2-phase Sub...mentioning
confidence: 99%
“…Since the melting point of ZrSi is close to the sintering temperature, it could result in partial melting during the sintering hold at temperature, and thus, a slight formation of the silicon (Si) phase as detected by XRD. The presence of ZrSi and Si phases along with the ZrSi 2 phase was similarly found in the Zr/Si diffusion couple after high-temperature annealing at 1200 °C [20]. Furthermore, Rietveld refinement results in the authors’ previous study [14] demonstrated that ~20.2 vol % of a secondary Mo 5 Si 3 phase formed in the [90–10] MoSi 2 -Al 2 O 3 composite after sintering.…”
Section: Resultsmentioning
confidence: 75%